DESAIN DAN ANALISIS CROSSING PIPA BAWAH LAUT DI LAUT JAWA - Muhammad I, Kautsar
The subsea pipeline system designed needs to be strong and safe from all possible failures that occur during installation, hydrotest and operational conditions. In general, failures that occur in the pipeline are due to the design of pipe wall thickness, pipe stability design, pipe free span design, and pipe tension design when installed using vessel pipelays. The design of pipe wall thickness based on DNV-OS F101 standard explains that the thickness of the pipe design must be sufficient to withstand working loads such as environmental loads and system pressure. Pipe stability design based on DNV-RP F109 and DNV-RP E305 explains that the pipe design must be in a stationary condition due to vertical and lateral loads. The configuration of the vessel pipelines needs to be designed, so that the pipe installation process does not produce excessive stress. A free span design based on DNV-RP F105 explains that the pipe has a free span that is permitted. Then, the pipeline system that operates along the seabed will face an obstacle. So that the pipeline route will not be stretched forever. One way to deal with the obstacle is by crossing the pipe. The thing that needs to be considered in pipe crossing is the height of the pipe crossing and natural pipe bending that occurs.